2018
DOI: 10.1186/s12884-018-1765-6
|View full text |Cite
|
Sign up to set email alerts
|

Cerclage is associated with the increased risk of preterm birth in women who had cervical conization

Abstract: BackgroundThe aim of this study was to determine the effect of cerclage in women who underwent cervical conization.MethodsStudy data were collected from the Korea National Health Insurance Claims Database of the Health Insurance Review and Assessment Service for 2009–2013. Women who had a conization in 2009 and a subsequent first delivery between 2009 and 2013 in Korea were enrolled.ResultsAmong the women who had conization in 2009, 1075 women had their first delivery between 2009 and 2013. A cerclage was plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
1
Order By: Relevance
“…Cho et al. reported that women who have undergone conization and cerclage are at higher risk of preterm birth than those who have not undergone cerclage [ 41 ]. The authors proposed that the higher risk may be attributable to inflammation after cervical cerclage and repeated trauma induced by conization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cho et al. reported that women who have undergone conization and cerclage are at higher risk of preterm birth than those who have not undergone cerclage [ 41 ]. The authors proposed that the higher risk may be attributable to inflammation after cervical cerclage and repeated trauma induced by conization.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, although the rates of preterm birth tended to be higher in women who had undergone cerclage following conization than in those who had not undergone cerclage in all age groups, these differences were not statistically significant. Cho et al reported that women who have undergone conization and cerclage are at higher risk of preterm birth than those who have not undergone cerclage [41]. The authors proposed that the higher risk may be attributable to inflammation after cervical cerclage and repeated trauma induced by conization.…”
Section: Discussionmentioning
confidence: 99%
“…After first-circle database searching, 261 articles were detected. Following reading and screening, we accepted nine studies to be included in our final metaanalysis [7][8][9][10][11][12][13][14][15]. Figure 1 illustrated the literature screening process.…”
Section: Information Retrievalmentioning
confidence: 99%
“… 10 However, those studies suffered from a small number of subjects. To overcome the limitation of small sample sizes, Cho, et al 11 used the claims database of the National Health Insurance Service (NHIS) of Korea to look at the risk of preterm birth after conization. 11 In the report, they included more than 1000 subjects and found that the cerclage is associated with an increased risk of preterm birth in women who have undergone conization.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the limitation of small sample sizes, Cho, et al 11 used the claims database of the National Health Insurance Service (NHIS) of Korea to look at the risk of preterm birth after conization. 11 In the report, they included more than 1000 subjects and found that the cerclage is associated with an increased risk of preterm birth in women who have undergone conization. However, the timing of the procedure may matter because if the cerclage was performed when they had symptoms of cervical insufficiency, such as cervical dilatation and bulging membranes, an increased risk of preterm birth may have already been present.…”
Section: Introductionmentioning
confidence: 99%